SOFT SKILL DIPERLUKAN DALAM RANGKA MENJEMBATANI KESENJANGAN ANTARA KOMPETENSI YANG DIMILIKI LULUSAN DENGAN KEBUTUHAN DUNIA KERJA - Heryati Heryati; Yeti Resnayati; Deswani Kasim (Poltekkes Kemenkes Jakarta III, 2013)
In order to increase the competitiveness and quality of University, it is necessary to attempt to determine indicators of college performance, one of which is the quantity and the quality and relevance of graduates to the workforce. This study aims to determine the relevance polytechnic graduates Jakarta III (Department of Nursing, Midwifery and Health Analyst) competencie with the required competencies in working world. The data collection tool was a questionnaire and explored with interviews and it analyze was performed with the interactive model, in the analysis of these 3 components analysis of data reduction, data presentation and conclusion or verification. This research method Tracer Study conducted descriptive survey approach. Subjects were graduated of nursing, midwifery and health analysts as much as 79 people. The data analysis technique used is descriptive analysis later described as a percentage of the graduate profile picture. The results obtained Jakarta polytechnic graduates Profile III in 2002-2011 and the need for soft skills such as English language ability, kamunikasi through elektrnik (mastery of computer and internet, audiovisual presentations, and communication tools), personal skills include self-reliance, communication skill and hear, brave, spirit and teamwork skills, initiative, and openness and flexibility and motivation to move forward is the ability to adapt to the changing times and environment as well as the desire to move forward as a leader.